Exploration of P-type Ca2+ channels as drug targets for the treatment of epilepsy or ischemic stroke. - Lingenhöhl, K; Small, D; Monette, R; Buchan, A; Morley, P; Allegrini, P; Fröst, L; Sauer, D; Schmutz, M; Knöpfel, T (1997)
We investigated the neuroprotective efficacy of the P-type Ca2+ channel antagonist daurisoline against electroshock-induced convulsions in rats and mice, hypoxic/hypoglycemic-induced damage in rat hippocampal slices and brain damage induced by occlusion of the middle cerebral artery (MCA) in rats. Daurisoline applied intravenously (i.v.) (bolus of 1-60 mg/kg) reduced the spontaneous activity of rat cerebellar Purkinje cells in a dose-dependent manner, a result demonstrating activity in the brain with systemic administration of the compound. While this effect reversed rapidly in about 10-20 min following bolus-application of the drug at doses of up to 30 mg/kg, a dose of 60 mg/kg consistently induced a depression of respiration followed by death of the animals. Daurisoline administered at 10-30 mg/kg did not prevent electroshock-induced convulsions in mice or rats, nor did it reduce the neuronal damage in hippocampal slices induced by a hypoxic/hypoglycemic insult in vitro by MCA occlusion in vivo. These observations do not support the hypothesis that P-type Ca2+ channels are promising drug targets for the acute treatment of epileptic convulsions and/or ischemic stroke.